Uncovering the temporal carbon isotope (δ13C) heterogeneity in seep carbonates: a case study from Green Canyon, northern Gulf of Mexico - Feng, Xia; Jia, Zice; Wang, Xudong (Frontiers in Marine Science, 2023)
Authigenic carbonates that form at hydrocarbon seeps, known as seep carbonates, are direct records of past fluid flow close to the seafloor. Stable carbon isotopes of seep carbonates (δ13Ccarb) have been widely used as a proxy for determining fluid sources and seepage mode. Although the spatial heterogeneity of δ13C in seep carbonates is increasingly understood, the temporal heterogeneity of δ13C in seep carbonates is not well studied. In this study, we report δ13C values of different components (clasts, matrix, and pore-filling cements) for 124 subsamples drilled across an authigenic carbonate block from Green Canyon block 140 (GC140) of the northern Gulf of Mexico continental slope. High-Mg calcite is the dominant mineral regardless the types of components. The δ13Ccarb values range from −39.6‰ to 3.6‰, indicating multiple dissolved inorganic carbon (DIC) sources that include methane carbon (13C-depleted), seawater DIC, and residual CO2 from methanogenesis (13C-enriched). Specifically, the clasts show large variability in δ13C values (−39.6‰ to 2.3‰; mean: −27.6‰, n = 71), demonstrating the dominance of methane-derived fluids during formation at the initial seepage stage. The δ13C values of the matrix vary between −29.4‰ and 3.4‰ (mean: −11.6‰, n = 21). The carbon isotopes of pore-filling cements that formed most recently vary narrowly, with δ13C values of −3.2‰ to 3.6‰ (mean: 1.7‰, n = 28). Isotopic variations within individual samples were observed in seep carbonate. However, common trends occur across components of carbonates that formed during different seepage stages. This suggests that the temporal evolution of local fluid sources may play an important role in determining carbonate isotope geochemistry. Studies regarding seeps must take into account the highly variable fluids that leave their geochemical imprints on the seep carbonate.